Pressure measurement characteristics of a micro‐transducer and balloon catheters. Issue 8 (2nd May 2021) - MacAskill, William; Hoffman, Ben; Johnson, Michael A.; Sharpe, Graham R.; Mills, Dean E.
Abstract: Respiratory pressure responses to cervical magnetic stimulation are important measurements in monitoring the mechanical function of the respiratory muscles. Pressures can be measured using balloon catheters or a catheter containing integrated micro‐transducers. However, no research has provided a comprehensive analysis of their pressure measurement characteristics. Accordingly, the aim of this study was to provide a comparative analysis of these characteristics in two separate experiments: (1) in vitro with a reference pressure transducer following a controlled pressurization; and (2) in vivo following cervical magnetic stimulations. In vitro the micro‐transducer catheter recorded pressure amplitudes and areas which were in closer agreement to the reference pressure transducer than the balloon catheter. In vivo there was a main effect for stimulation power and catheter for esophageal (Pes ), gastric (Pga ), and transdiaphragmatic (Pdi ) pressure amplitudes ( p  < 0.001) with the micro‐transducer catheter recording larger pressure amplitudes. There was a main effect of stimulation power ( p  < 0.001) and no main effect of catheter for esophageal ( p  = 0.481), gastric ( p  = 0.923), and transdiaphragmatic ( p  = 0.964) pressure areas. At 100% stimulator power agreement between catheters for Pdi amplitude (bias =6.9 cmH2 O and LOA −0.61 to 14.27 cmH2 O) and pressure areas (bias = −0.05 cmH2 O·s and LOA −1.22 to 1.11 cmH2 O·s) were assessed. At 100% stimulator power, and compared to the balloon catheters, the micro‐transducer catheter displayed a shorter 10–90% rise time, contraction time, latency, and half‐relaxation time, alongside greater maximal rates of change in pressure for esophageal, gastric, and transdiaphragmatic pressure amplitudes ( p  < 0.05). These results suggest that caution is warranted if comparing pressure amplitude results utilizing different catheter systems, or if micro‐transducers are used in clinical settings while applying balloon catheter‐derived normative values. However, pressure areas could be used as an alternative point of comparison between catheter systems. Abstract : The aim of this study was to provide a comparative analysis of micro‐transducer and balloon catheter pressure characteristics: (1) in vitro with a reference pressure transducer; and (2) in vivo following cervical magnetic stimulations. In vivo there was a main effect for catheter for esophageal, gastric, and transdiaphragmatic pressure amplitudes and no main effect for pressure areas, indicating that pressure areas could be used as a point of comparison between catheter systems. Caution is warranted if comparing pressure amplitude results from different catheter systems or if micro‐transducers are used in clinical settings with balloon catheter‐derived normative values.